Research lines in mining in the 21st century: A retrospective and bibliometric analysis of the literature from an environmental perspective - Robles, Ruth (Iberoamerican Journal of Science Measurement and Communication, 2022)
Objective. This article develops a bibliometric study to find out what are the lines of research that analyze mining activity in the 21st century and to find out how many documents on mining have been published, what research areas they cover, as well as who the authors, magazines, organizations, and countries that have published the most. Design/Methodology/Approach. The study analyzes and maps the topics covered by 1,791 documents published in the Scopus database from 2000 to 2019, based on the keywords defined by the authors in their publications, which were later recognized as lines of research. For this, the VOSviewer version 1.6.15 program was used. Results/Discussion. The study identified 44 research lines in seven research groups, of which five are directly related to the effects that mining produces on the environment. In particular, two lines of research stand out: Environmental impact and Economic, ecological and social effects, which account for 25% of the occurrences determined in the study. Conclusions. There is an upward trend in the publication of mining documents in the Scopus database. Notably, research focuses mainly on studying the impacts caused by this activity on the environment and society and its possible solutions. Originality. This study establishes a frame of reference for studying mining activity in the 21st century.